Slang in American and British Hip-Hop/Rap Song Lyrics - Tessa Zelyana Hidayat; Rio Rini Diah Moehkardi (Universitas Gadjah Mada, 2018)
This research examines semantic changes and also the associative patterns of slang, focusing primarily on common topics, i.e., people and drugs. The data were slang terms taken from the lyrics of hip-hop/rap songs sung by four singers, two from the U.S.A and two from the U.K. A total of 105 slang terms were found, 45 of which belong to the people category and 16 to the drugs category in the American hip-hop/rap song lyrics, and in the British hip-hop/rap song lyrics, 26 of which belong to the people category and 18 to the drugs category. Bitch and nigga were found to be the most frequently used slang terms in the people category. In terms of semantic changes, broadening, amelioration, and narrowing were found, and in terms of associative patterns, effect, appearance, way of consuming, constituent, and container associative patterns were found. In addition, a new associative pattern was found, i.e., place of origin.